2018
DOI: 10.1021/jacs.8b10866
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Goldberg Polyhedra from a Concave [WV5O11(RCO2)5(SO4)]3– Building Block with 5-Fold Symmetry

Abstract: Nanoscale regular polyhedra with icosahedral symmetry exist naturally as exemplified by virus capsids and fullerenes. Nevertheless, their generation by supramolecular chemistry through the linking of 5-fold symmetry vertices remains unmet because of the absence of 5-fold symmetry building blocks with the requisite geometric features. This situation contrasts with that of tetrahedral and octahedral symmetry metal–organic polyhedra (MOPs), for which appropriate triangular and square molecular building blocks (MB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…4c, d). Thus, it can be concluded that an ion-exchange process occurred between the cationic dyes and [NH 2 Me 2 ] + cations 37 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…4c, d). Thus, it can be concluded that an ion-exchange process occurred between the cationic dyes and [NH 2 Me 2 ] + cations 37 .…”
Section: Resultsmentioning
confidence: 96%
“…Given that the inner and outer cages in 1 are independent and assembled by supramolecular interactions, we try to obtain their discrete objects. On the basis of our research experience about polyoxovanadate-based MOPs 37,38 , the inner cage, (NH 2 Me 2 ) 12 [(V 5 O 9 Cl) 6 (TATB) 8 ]•(CH 3 OH) 4 (1a), was successfully isolated in high yield by reaction of VCl 4 , VOSO 4 , and H 3 TATB in DMF:CH 3 CN:CH 3 OH (4:1:1 v/v) at 130°C for 48 h (see the "Methods" section for a detailed synthesis procedure). Singe-crystal diffraction revealed that 1a crystallized in cubic system with space group Fm-3m (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the peaks and did not find the molecular ion peak of the cluster.The difference between 3a-3c and 3a' '-3c' ',corresponding to Dy 76 in mixed solutions of CH 3 Thev ariable-temperature magnetic susceptibilities of Dy 76 and Dy 48 were measured from 2-300 K. As shown in Figure S4, the c m T values are 1032.3 cm 3 Kmol À1 for Dy 76 and 650.6 cm 3 Kmol À1 for Dy 48 at 300 K, which are close to the expected values of 1076.9 and 680.16 cm 3 Kmol À1 for 76 and 48 isolated Dy III ions with atotal angular momentum M J = 15/ 2a nd aL andØ g factor g = 4/3. [16] When the temperature was reduced from 300 to 100 K, the c m T values of Dy 76 and Dy 48 slightly decreased, and the values reached 1000.1 and 629.4 cm 3 Kmol À1 ,r espectively,a t1 00 K. Upon further lowering the temperature,t he c m T values abruptly decreased to minimum values of 592.5 and 363.6 cm 3 Kmol À1 for Dy 76 and Dy 48 ,respectively,at2K. These findings indicate the presence of weak antiferromagnetic interactions.…”
Section: Methodsmentioning
confidence: 99%
“…The4 -c metal SBU has been used earlier to construct MOPs by Zaworotkos, Schmittsand our group. [9] In addition, the double SBUs( 4-c and 5-c SBUs) are found in one MOP for the first time. [9] In addition, the double SBUs( 4-c and 5-c SBUs) are found in one MOP for the first time.…”
mentioning
confidence: 91%